Anti-money laundering provisions in the light of EU directives - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Money laundering is one of the most serious white collar crimes that jeopardizes the proper functioning of the broad spectrum of business transactions, not only at the internal level but also at the international or even global level. Therefore it is extremely important to counteract money laundering at a wider than national level. Within the European Union complex anti-money laundering provisions are included in four EU Directives, which are covered in this article.
Keywords: Dyrektywa UE; pranie pieniędzy; przestępstwo; przeciwdziałanie praniu pieniędzy; AML